Performance metrics that matter: assessing winning and losing teams in women`s Rugby union - Callinan, M. J.; Connor, J. D.; Sinclair, W. H.; Gómez, M.-Á. (International Journal of Performance Analysis in Sport, 2024)
The aim of this study was to identify key performance indicators (KPI) that differentiated winning and losing teams, and how KPI may vary in balanced and unbalanced matches in Australian domestic women`s Rugby Union (RU). Four seasons of the Buildcorp Super W competition (2019-2022), round and final matches (n = 47) were analysed by an experienced performance analyst using computerised notational analysis software (Hudl SportsCode) to identify various KPI that occurred throughout a match. Findings showed that winning teams had greater ball-carrying efficiency, quick ruck speed, greater field-based tactics, greater successful conversions, and created more scoring opportunities while losing teams had poorer goal-kicking performance, greater number of rucks lost, and unsuccessful set piece performance. However, in balanced matches, only greater scoring opportunities, possession, and kicking performance discriminated between winning and losing teams. Winning teams in unbalanced matches had greater scoring opportunities, kicking performance, possession, territory, ball-carrying efficiency, and ruck performance, whilst losing teams had a greater number of rucks lost and lineouts lost. These results suggest some performance metrics can differ between balanced and unbalanced matches. Coaches may use these findings to help evaluate match performances based on scoring differential, as well as influence possession-in-territory, and kicking tactics, to increase scoring opportunities.